Using a Mental image with a Motor rhythm and Their Effect on Control a motion of breath and arms in free style swimming - salah aldean, mustafa (Journal of Physical Education, 2010)
The problem of the research lied in learning a control of breath with arms motion , and late a development of student ability to learn a two motions and swimm a distance . The aim of the study is to identify the efect of using a mental image with motor rhythm on control a motion of breath and arms in free style swimming . The researcher used the experimental method to achieve the hypothesis of the research . The researcher hypothesized the existence of positive effect after using a mental image with motor rhythm on Control a motion of breath and arms in free style swimming. The subjects were (40) first year college of physical education students. They were divided into two equal groups; the controlling group and the experimental group. the experimental group that used the exercises of mental image with motor rhythm in learning but the controlling group that did not use them . The researcher used a test of breath with arms motion to know a level of subjects in free styl swimming . after the data was collected and treated statistically using t ــ test ‚ the researcher concluded that the controlling motion of breath with arms can be developed using a mental image with motor rhythm exercises during a learning swimming . Finally‚ the researcher recommended to using a mental image with motor rhythm exercises to learn students controlling of breath and arms motion in free styl swimming . He also recommended making similar researches using a mental image with motor rhythm exercises to develop other motion and other types of swimming stroke .